ANALISIS NILAI KARAKTER SISWA DALAM KEGIATAN BULAN BAHASA - Prihmukti Setyo Hastuti; Mira Azizah; Ferina Agustini (Universitas Negeri Medan, 2023)
Abstract: During the Covid-19 pandemic, learning was carried out online. The long-lasting covid-19 pandemic has caused a moral/character crisis. Character education can be obtained through school. Efforts made through language month activities. The purpose of this study was to describe the character values of students who appeared in the Language Month activities at SD Negeri Karangrejo. Data collection through interviews with school principals, observation of activities and documentation. Qualitative research methods with a descriptive approach to data analysis used include: reduction, data presentation, and drawing conclusions. The subjects of this study were all students of SD Negeri Karangrejo 01 Semarang City. The results of this study in the Language Month activities are religious character values.Keyword: Character Values, Students, Language MonthAbstrak: Pandemi Covid-19 pembelajaran dilaksanakan secara daring. Pandemi covid-19 yang berlangsung lama menyebabkan krisis moral/karakter. Pendidikan karakter dapat diperoleh melalui sekolah. Upaya yang dilakukan melalui kegiatan bulan bahasa. Tujuan dalam penelitian ini adalah untuk mendeskripsikan nilai karakter siswa yang muncul dalam kegiatan Bulan Bahasa Di SD Negeri Karangrejo. Pengumpulan data melalui wawancara kepala sekolah, observasi kegiatan dan dokumentasi. Metode penelitian kualitatif dengan pendekatan deskriptif Analisis data yang digunakan, antara lain: reduksi, penyajian data, dan menarik kesimpulan. Subyek penelitian ini seluruh siswa SD Negeri Karangrejo 01 Kota Semarang. Hasil dari penelitian ini dalam kegiatan Bulan Bahasa adalah nilai karakter religius.Kata Kunci: Nilai Karakter, Siswa, Bulan Bahasa